Building urban climate resilience: An inclusive approach to heat stress mapping and capacity building in Ayodhya, India - Farheen Bano; Abirbhav Sanyal; Vandana Sehgal; Ritu Gulati; Gaurav Singh; Jente Broeckx; Ibrahim Hafeezur Rehman; Raf Theunissen; Tomas Crols; Shu Yang (Green Technologies and Sustainability, 2025)
Urban areas are increasingly vulnerable to the impacts of climate change, necessitating robust and inclusive approaches to enhance resilience, which in turn demands sufficient public and governmental awareness and understanding of climate change. This study focuses on Ayodhya, a fast-developing city in India, and employs a comprehensive methodology to build climate resilience through capacity building of faculty, students, stakeholders, and dissemination efforts targeting the public and school children. The methodology integrates training workshops, collaborative projects, and public outreach to foster an understanding of climate resilience principles and practices.By empowering local communities and institutions with knowledge and tools to address climate challenges, the study demonstrates significant improvements in preparedness and adaptive capacity. A key component of the research involved heat stress mapping in Ayodhya, utilizing Geographic Information Systems (GIS) to identify high-risk areas and analyze patterns of heat exposure. Future projections of heat stress and temperature, validated with participatory in-situ measurements, were generated using climate models, providing critical data to inform adaptive strategies.Key findings include significant improvements in preparedness and adaptive capacity, driven by a multi-faceted approach to capacity building. The paper highlights two primary outcomes: detailed results on heat exposure in Ayodhya, obtained through GIS mapping and climate models, and the analysis of methodologies employed for capacity building. Heat stress mapping identified high-risk areas and patterns of heat exposure and validated with participatory in-situ measurements. The paper underscores the importance of inclusive and participatory methods in urban climate resilience planning and offers a replicable model for other rapidly urbanizing regions facing similar challenges.